THE NATIONAL GENDER POLICY’S AFFIRMATIVE ACTION: AN ASSESSMENT OF THE CHALLENGES TO WOMEN REPRESENTATION IN CABINET POSITIONS IN NIGERIA - Salaudeen, Abdulkadir; Jiddere, Abubakar Jika (The Gender Truth Journal, 2024)
Affirmative action for women is an outcome of global advocacy for gender mainstreaming in politics and decision-making processes. Through the instrumentality of some gender-friendly treaties, to which many countries—including Nigeria—are signatories, countries are encouraged to allot women a certain percentage in political appointments. Thus, women’s visibility in modern state politics is increasingly becoming a yardstick to measure levels of democratization and sustainability of democracy. Countries across the globe, including the most conservative, are making both minor and radical changes to address gender issues. This explains why the Nigerian Government came up with its National Gender Policy (NGP) in 2006. This Policy advocated for 35% affirmative action to women in all political appointment positions in consonance with global efforts to address women’s marginalization and discrimination, as captured in the 1979 Convention on the Elimination of All Forms of Discrimination Against Women and the 1995 Beijing Declaration. However, women are still being marginalized in Nigerian politics due to the age-long patriarchal notion that women are not meant for public affairs, thereby making the domestication of gendered affirmative action policy in a patriarchal society like Nigeria problematic. Methodically, this study is both qualitative (using discourse analysis) and quantitative (analyzing numerical data on women in cabinet positions across the federating units). From the perspectives of political liberalism and feminist legal theory, this study critiques the concept of affirmative action vis-a-vis women’s representation in cabinet positions in Nigeria. The study findings reveal that the Constitutional barrier has been the major stumbling block to the implementation of Nigeria’s Affirmative Action since 2006. The study concludes that unless Affirmative Action is enshrined in the Constitution, its implementation will be at the mercy of the disposition of the government in power. Thus, this study recommends Constitutional reforms to accommodate crucial gender decisions made by the government such as Affirmative Action to facilitate its implementation.